El ímpetu de la primavera y la sonrisa del otoño (2021)
An investigation of the history of armed or edited life of the teacher Cristian Rafael Pacheco Arrieta will be carried out, of a descriptive explanatory type, with a qualitative approach, having as referenced sources, primary sources that we will approach with closed semistructured interviews, which will be added to the others information gathering techniques, such as structured interviews and journalistic documentation. Family, friends, fellow dance and plastic arts artists and students of the teacher will be considered as the universe of the investigation.